Frequency Reconfigurable elliptical microstrip patch antenna using resonator, partial removal in the ground, and PIN diode for L and C band applications. Issue 1 (February 2021) - Amarnatha Sarma, Ch.; Inthiyaz, Syed; Madhav, B T P; Sree Lakshmi, P
Abstract: In this proposal a frequency reconfigurable elliptical patch antenna is proposed for L and C and application. A PIN diode with resonator is used to get the frequency switching. It has its bandwidths of 2 GHz and 2.5 GHz respectively in L and C bands when diode is OFF and band width of 3.7GHz in C band when diode is ON. The proposed model is simulated using commercial RF tool-HFSS. The substrate used in simulation is economical FR4 with 4.2 dielectric constant value and 1.6mm height having dimensions 40mm X 42mm in which the patch is 20mm X 40mm. The return loss (S11), VSWR, radiation pattern, E and H plane field strengths are obtained and the constructive simulated results mentioned, which are show the switching in frequency operation.